THE TALIBAN & AFGHANISTAN: CONFLICT & PEACE IN INTERNATIONAL LAW PERSPECTIVE - Amini, Ma'ruf; Arifani, Devina (International Journal of Law Reconstruction, 2021)
This study aims to determine the political situation in Afghanistan which is now occupied by the Taliban. This qualitative research method is often called "naturalistic research method" because the research is carried out in natural conditions (natural setting). In this study, researchers used two kinds of data, namely primary data and secondary data. To determine the validity of the data, an inspection technique is needed. The implementation of the inspection technique is based on a number of certain criteria. There are four criteria used, namely the degree of trust (credibility), transferability, dependence (dependability), and certainty. The conclusions of this study are; 1) The Taliban insists that it is committed to peace talks with the Afghan government. The implementation of the original Islamic system will be something they strive for. 2) The Taliban is committed to accommodating all the rights of citizens, whether male or female, based on the noble religious rules of Islam and the noble traditions of Afghan society. The Taliban will allow women to carry out public roles. 3) Advancing a better Afghanistan.